Digital phase diagram and thermophysical properties of KNO3-NaNO3-Ca(NO3)2 ternary system for solar energy storage. (November 2017) - Chen, Mengmeng; Shen, Yuesong; Zhu, Shemin; Li, Peiwen
Abstract: The molten nitrate salt has become one of the most promising heat storage and transfer medium for solar energy. A series of molten salt systems containing KNO3 -NaNO3, Ca(NO3 )2 -NaNO3, KNO3 -Ca(NO3 )2 and KNO3 -NaNO3 -Ca(NO3 )2 were designed and prepared to study the liquidus surface, and the thermal stability of the KNO3 -NaNO3 -Ca(NO3 )2 ternary system was mainly studied. A 3D stable molten temperature diagram was developed to predict melting points and thermal decomposition points in the KNO3 -NaNO3 -Ca(NO3 )2 ternary system, as well as its eutectic temperature and composition. The predicted eutectic composition is 42% KNO3 -17% NaNO3 -41% Ca(NO3 )2, which has a low predicted melting point of 129.1 °C and a high predicted decomposition temperature of 597.9 °C. Moreover, a series of melting points and thermal decomposition points obtained from the 3D stable molten temperature diagram were respectively verified experimentally using thermo-gravimetric (TG) and differential scanning calorimetry (DSC) methods. The experimental results were in excellent agreement with that of obtained values from the 3D stable molten temperature diagram. Highlights: A 3D stable molten temperature diagram of the system (K, Na, Ca/NO3 ) is developed. The eutectic composition and temperature span of the system were predicted. The predicted eutectic composition is 42% KNO3 -17% NaNO3 -41% Ca(NO3 )2 . The predicted eutectic mixture has a wide temperature span from 129.1 to 597.9 °C.